Microsponge based drug delivery system for augmented gastroparesis therapy: Formulation development and evaluation - Riyaz Ali M. Osmani; Nagesh H. Aloorkar; Bharati U. Thaware; Parthasarathi K. Kulkarni; Afrasim Moin; Umme Hani; Atul Srivastava; Rohit R. Bhosale (Elsevier, 2015)
The intention behind the present work was to develop a microsponge based novel dosage form for sustained delivery of domperidone. Quasi-emulsion solvent diffusion method was employed using Eudragit RS-100 with various drug-polymer ratios for the preparation of microsponges. For optimization purposes, several factors which affect microparticles' physical properties were investigated. Characterization techniques followed for the formed microsponges were DSC, FTIR, SEM, XRD and particle size analysis, along with morphology, drug loading and in vitro drug release. It was found that there were no chemical interactions between drugs and polymers used as per DSC and FTIR results. The drug-polymer ratio showed remarkable impact on drug content, encapsulation efficiency and particle size. SEM micrographs revealed that microsponges were spherical in shape with porous surface, and had 104 ± 0.22 µm mean particle size. The microsponges were then loaded in capsules followed by in vitro drug release study; which depicted that microsponges with drug-polymer ratio of 1:2 were more proficient to give extended drug release of 76.38% at the end of 8 h, superior in contrast to conventional marketed formulation Domstal®, which got exhausted incredibly earlier by releasing 82.57% drug at the end of ½ h only. Hence, the developed microsponge based formulation of domperidone would be an expectant, promising substitute to conventional therapy of gastroparesis, emesis and alike gastric ailments.